A clinical evaluation of skin tags in relation to obesity, type 2 diabetis mellitus, age, and sex - Omar Soliman El Safoury; Magdy Ibrahim (Wolters Kluwer Medknow Publications, 2011)
Background: Skin tags (STs) have been investigated as a marker of type 2 diabetes mellitus (DM), yet the relation of STs to obesity is still a matter of controversy. Aim : The aim of the study is to explore the relation of number, size and color of STs to obesity, diabetes, sex and age in one study. Methods: The study included 245 nondiabetic (123 males and 122 females) and 276 diabetic (122 males and 154 females) subjects. We recorded age, sex, body mass index (BMI), relevant habits, STs color, size, and number in different anatomical sites. Results: The presence and the mean number of STs was more in obese than nonobese participants (P = 0.006 and P < 0.001, respectively) and was not affected by sex. However, the number increased significantly with age. The presence of mixed-color STs was related to obese (P < 0.001) participants. Multivariate logistic regression revealed that only BMI was significantly associated with the mixed-color STs (OR = 3.5, P < 0.001). The association of DM (OR = 1.7) with mixed-color STs was nonsignificant (P = 0.073). Neither age nor sex had any association with mixed-color STs. Within cases that developed mixed-color STs, the multivariate analysis showed that only BMI had a significant correlation to the number of STs (beta = 0.256, P = 0.034). Conclusion: The study showed that not only the number but also the presence of mixed-color ST was related to obesity, but not to diabetes. The presence of mixed-color STs in nondiabetic subjects needs close inspection of BMI.